Enantioselective Bio‐Hydrolysis of Geranyl‐Derived rac‐Epoxides: A Chemoenzymatic Route to trans‐Furanoid Linalool Oxide. Issue 4 (28th December 2018) - van Lint, Matthijs J.; Gümüs, Aysegül; Ruijter, Eelco; Faber, Kurt; Orru, Romano V. A.; Hall, Mélanie
Abstract: In contrast to many chemical dihydroxylation methods, enzymatic epoxide hydrolysis provides an environmentally benign route to vicinal diols, which are important intermediates in the synthesis of fine chemicals and pharmaceuticals. Using epoxide hydrolases, enantiopure diols are accessible under mild conditions. In order to assess the selectivity of epoxide hydrolases on geraniol‐derived oxiranes, a range of derivatives were screened against a large variety of enzyme preparations. For nearly all substrates, a matching hydrolase with excellent enantioselectivity (≥95% ee ) could be found. In addition, a chemoenzymatic approach for the stereoselective synthesis of furanoid linalool oxide was developed. Combination of enzymatic enantioselective hydrolysis with stereoselective Tsuji‐Trost reaction granted diastereoselective access to trans ‐(2 R, 5 R )‐configured linalool oxide with high diastereomeric and enantiomeric excess (97% de and 97% ee ). Abstract :